PERAN PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN (PUAP) TERHADAP KESEJAHTERAAN PETANI DI DESA POLAGAN, KECAMATAN GALIS, KABUPATEN PAMEKASAN - Siti Ienas Maulidia; Herry Yulistiyono (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2020)
The agricultural sector is still experiencing structural changes that are not balanced. To overcome this, the Government through the Department of Agriculture issued a policy in an effort to empower the community in the form of PUAP's Direct Community Assistance (BLM) facilitation program. The purpose of the study was to analyze the role of the Rural Agribusiness Development Program (PUAP) on the welfare of farmers in Polagan Village, Galis District, Pamekasan Regency. The research method used is descriptive qualitative. Data collection methods using interviews, observation, and documentation. Descriptive analysis model analysis technique with data validity test is done by using triangulation of data sources. The results showed that the implementation of the Agribusiness Business Development program in Polagan Village, Galis Subdistrict, Pamekasan Regency was good because the distribution process to farmers was in accordance with procedures so that farmers could be used for capital to develop farming. The level of welfare of farmers in Polagan Village, Galis District, Pamekasan Regency as a whole is still low. the role of the Rural Agribusiness Development Program (PUAP) on the welfare of farmers in Polagan Village, Galis District, Pamekasan Regency has not been maximized in terms of targets, techniques, and objectives. Recommendations are that the PUAP program should not only be in the form of agricultural capital loans but through other new innovations. Like the provision of subsidized fertilizer.